The significance of the Yamoussoukro Decision in the recovery of the civil aviation market in Africa post the COVID-19 pandemic : a consideration of the meaningful impact of the African airspace - Hobe, Stephan (University of Pretoria, 2024)
Dissertation (LLM (International Air Space and Telecommunications Law))--University of Pretoria, 2023.